SurveySum: A Dataset for Summarizing Multiple Scientific Articles into a Survey Section - Fernandes, Leandro Carísio; Guedes, Gustavo Bartz; Laitz, Thiago Soares; Almeida, Thales Sales; Nogueira, Rodrigo; Lotufo, Roberto; Pereira, Jayr (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2024: Anais da XXXIV Brazilian Conference on Intelligent Systems, 2024)
Document summarization is a task to shorten texts into concise and informative summaries. This paper introduces a novel dataset designed for summarizing multiple scientific articles into a section of a survey. Our contributions are: (1) SurveySum, a new dataset addressing the gap in domain-specific summarization tools; (2) two specific pipelines to summarize scientific articles into a section of a survey; and (3) the evaluation of these pipelines using multiple metrics to compare their performance. Our results highlight the importance of high-quality retrieval stages and the impact of different configurations on the quality of generated summaries.